Analysis of Regional Financial Capability Before and After Expansion of the Provincial (Studies in District / City in the Province of North Kalimantan) - Adha Pramidaya Haji (Institute of Research and Community Service, University of Brawijaya)
AbstractThe purpose of study is to give empirical evidence the financial capability based on the share, growth, Financial Capability Index (IKK) regional, local revenue and expenditure districts/cities in North Kalimantan before and after expansion of the province. This study uses a mixed method with secondary data of local government budget (APBD) and Gros Domestic Product (GDP) budget 5 (five) districts/cities in North Kalimantan by time series 2010 to 2015 for quantitative analysis. There are 6 samples of informants from 3 districts/cities for the analysis of qualitative descriptive with interviews methods. T-test results of share, growth index and IKK aren’t difference before and after expansion of the province. Based on the results of qualitative analysis has found an average decrease in share, growth index and IKK. Share index down because of local own source revenue (PAD) is not designed as a primary source of APBD, growth index down because of district/city uses deposits to increase PAD so after expansion of the province, the deposit is used to cover the APBD deficit. IKK decrease occurred because the district/city tends to depend on the balancing of funds after the expansion of the province. The result of t-test local revenue and expenditure had better difference after expansion of the province. The results of qualitative analysis, indicate an increase in local revenue and expenditure that is occurred only two years early expansion because of political reasons and after the third years APBD had decrease is due to DBH Migas dropped dramatically. Differences results of this analysis are influenced by political interests of each province.This study proves that the expansion of the province is not short-term solutions for the acceleration of development in the district / city in North Kalimantan. Keywords: Financial Capability Index; local revenue; local expenditure; expansion of province